Vos House : Amsterdam, he Netherlands 1999 - Van Velsen, Koen (2000)
Viviendas con fachada hacia un canal, en el puerto de Amsterdam
Keywords: PAISES BAJOS; AMSTERDAM; VIVIENDAS UNIFAMILIARES; PUERTOS